Imperfect competition, state trading and Japan's imports of rice - Donald MacLaren (Osaka University, Institute of Social and Economic Research (ISER), 2011)
In the negotiations on agriculture in the World Trade Organization, it was asserted that an importing state trading enterprise affects the domestic market but not the international market. This claim is investigated through specifying a model of intermediaries in international trade. There are two kinds of intermediaries: first, a state trading enterprise; and second, an n-firm Cournot oligopsony/oligopoly that acts as the counterfactual. Using Japanese market price and quantity data for rice, and elasticity parameters drawn from the literature, the equations of the model are calibrated to these data and parameters. The resulting equations then permit the calculation of the tariff equivalence of the state trading enterprise under different assumptions about market structure, as well as the welfare effects associated with them. The equations are re-specified to model the existing import regime for rice, which is a tariff quota. The conclusions are: first, that, compared with the counterfactual, an importing state trading enterprise acts like a tariff by restricting imports; and second, the current import regime of a tariff quota causes a welfare loss compared with the counterfactual.
Keywords: F12; F13; Q17; 330; state trading; Japan; rice; international intermediaries; Reis; Import; WTO-Recht; Importquote; Außenhandelselastizität; Wohlfahrtsanalyse; Japan